English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

D(out) = D(in) = 250t = 250 * (4 - t)
250t = 1000 - 250t
500t = 1000
t = 2

2006-12-14 10:00:27 · answer #1 · answered by roynburton 5 · 0 0

D/out = 250t
D/in = 250 x (4 - t)
with D/out = D/in

As D/in = D/out we can say mathematically that

250t = 250 x (4 - t)

Expanding the brackets using the distributive rule which states
a(b-c) = ab - ac
We can say mathematically that

250t = (250 X 4) - (250 X t)

therefore

250t = 1000 - 250t

Adding 250t to both sides of the equation gives

250t + 250t = 1000 (the 250t's cancel out on this side)

therefore adding the t's gives

500t = 1000

Therefore dividing both sides of the equation by 500 gives

t = 2

QED

2006-12-14 10:20:09 · answer #2 · answered by Gaz 5 · 0 0

D/out = D/in so 250t=250(4-t) so250t=1000-250t and so
(250+250)t=1000 so 500t=1000 so t=2

2006-12-15 07:46:38 · answer #3 · answered by keyur vyas 1 · 0 0

D/out = D/in
250t = 250(4 - t)
250t = 1000 - 250t
500t = 1000
t = 2

2006-12-14 10:10:58 · answer #4 · answered by Kemmy 6 · 0 0

fedest.com, questions and answers